Local Usage of Tiger Parts and Its Role in Tiger Killing in the Bangladesh Sundarbans. Issue 2 (3rd March 2016) - Saif, Samia; Russell, Aal M.; Nodie, Sabiha I.; Inskip, Chloe; Lahann, Petra; Barlow, Adam; Barlow, Christina Greenwood; Islam, A.; MacMillan, Douglas C.
ABSTRACT: This article explored the local medicinal and traditional values of tiger parts and associated beliefs, and its link to the commercial trade in the Bangladesh Sundarbans. Using semi-structured qualitative interviews with 139 respondents, we found that the local use of, and belief in, the medicinal values of tiger parts is widespread and that virtually all parts of the tiger are used. Some of the local uses of tiger parts were unique in both the way and the purpose of use. For example, the soil of tiger pugmark was consumed by the women as a means of contraception. We established that local usage may be a significant threat to the tiger population of south Asia as it motivates stray tiger killing for collecting tiger parts for both local use and commercial demand, and provides the opportunities for poachers and the commercial trade to flourish.